The Role of Euphemisms in Medical Communication (Texas Journal of Philology, Culture and History, 2022)
The article briefly characterizes use of euphemisms in the professional medical sphere; it describes techniques to create euphemisms.The article also covers ethical problems of euphemisms use in the speech of health care professionals.